A CRISPR-Cas12b–Based Platform for Ultrasensitive, Rapid, and Highly Specific Detection of Hepatitis B Virus Genotypes B and C in Clinical Application - Chen, Xu; Tan, Yan; Wang, Shuoshi; Wu, Xueli; Liu, Rui; Yang, Xinggui; Wang, Yi; Tai, Jun; Li, Shijun (Frontiers in Bioengineering and Biotechnology, 2021)
Hepatitis B virus (HBV) is one of the most dangerous and prevalent agents that causes human acute and chronic liver diseases. Genotyping play an important role in determining of clinical outcomes and response to antiviral treatment in HBV-infected patients. Here, we firstly devised a CRISPR-based testing platform, termed CRISPR-HBV, for ultrasensitive, highly specific, and rapid detection of two major HBV genotypes (HBV-B and HBV-C) in clinical application. The CRISPR-HBV employed multiple cross displacement amplification (MCDA) for rapid pre-amplification, and then Cas12b-based detection for decoding the targets. Finally, the detection result was reading out with real-time fluorescence and lateral flow biosensor (LFB). The sensitivity of CRISPR-HBV was 10 copies per test. The specificity was one hundred percent, and has no cross reactions were observed in in other HBV genotypes and pathogens. The whole detection process, including DNA template extraction (15 min), MCDA pre-amplification (30 min at 65ºC), CRISPR-Cas12b-based detection (5 min at 37ºC) and results reading (~2 min), could be completed within 1 h. The feasibility of CRISPR-HBV assay for genotyping of HBV-B and -C were successfully validated with clinical samples. Hence, the CRISPR-HBV assay has great potential to develop a point-of-care (POC) testing for identifying and distinguishing HBV genotypes B and C in clinical settings, especially in resource scarcity countries.